Optimal control of electric vehicles charging in a smart parking. Issue 5 (2022) - Aicardi, M.; Casella, V.; Ferro, G.; Minciardi, R.; Parodi, L.; Robba, M.
Abstract: The presence of electric vehicles (EVs) in the transportation systems has faced an outstanding increase in the last years and is expected to grow more and more thanks to the large number of incentives promoted by the different countries. This increase has some drawbacks and a lot of studies must be developed to find optimal solutions for the integration of these EVs into the pre-existing electrical system. In this paper, the focus is on power management strategies in a public smart charging park (SCP) characterized by renewables, storage systems, and different kinds of charging stations (CSs), both classical and V2G. EVs are supposed to be already allocated and present at the CSs. Power management aims to satisfy the demands of EVs without delays. Moreover, some reference values on the power purchased from the grid and the use of the storage are considered. The results show that the system is able to satisfy the energy request before the due date and the CSs with V2G are used to reduce the power purchased from the grid during the day.